Political reading as a means of understanding the Old Testament - Snyman, Fanie (Old Testament essays, 1994)
Special Edition: Understanding the Old Testament in South Africa. The aim of this paper is to demonstrate that a political reading of the Old Testament is and has been done from various angles in South Africa and that the different political readings share some similarities. Over and above obvious and irreconcilable differences between liberation theology and apartheid theology, there are also interesting similarities, some of which are highlighted. A word of caution is sounded to be careful and not simply claim the support of the Old Testament for one's political convictions. One should rather allow the Old Testament to be critical of one's political convictions, rather than legitimise them from the Old Testament.